Design and Validity of Electronic Assessment to Assess Students’ Critical Thinking Abilities on Rectilinear Motion Topic - Elvi Tiarahmah; Fatni Mufit; Letmi Dwiridal; Fuja Novitra (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2026)
Learning in the 21st century must include 4C skills, including critical thinking skills, especially in physics learning. Students' critical thinking skills need to be assessed to prepare them for the 21st century. Assessment instruments that specifically evaluate students' critical thinking skills on linear motion material are not yet available. Therefore, this study aims to develop a valid electronic assessment to evaluate students' critical thinking skills on linear motion material. This research is a development study (R&D) using the Plomp model. The data collection instruments used were interview sheets, self-evaluation sheets, and validation sheets. The electronic assessment developed was validated by three validators. Electronic assessment has a high validity category in terms of content, learning design, visual communication, and software usage, according to the validity analysis results. Based on the validation results with an average score of 0.85, it indicates that the electronic assessment used to evaluate students' critical thinking skills on the topic of linear motion is considered valid and suitable for use for use in assessing students' critical thinking skills.